2000
DOI: 10.1139/b00-097
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Douglas-fir by Leptographium wageneri

Abstract: Abstract:In three related experiments, root systems of 2-year-old Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) seedlings were dip-inoculated with a viscous blend of Leptographium wageneri var. pseudotsugae Harrington and Cobb spores and hyphal fragments and planted in a sterile potting medium. Infection frequency and points of entry were evaluated for dormant seedlings and seedlings that had been active for 4 and 8 weeks. All putative black stain infections and other areas of sapwood discoloration were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Such sites are reportedly used by some Rhizobium species (e.g. Gopalaswamy et al ., 2000; Vega‐Hernandez et al ., 2001) and fungi (Hessburg & Hansen, 2000; Lagopodi et al ., 2002) to invade hosts. However, these epidermal cracks may not occur naturally in the field or may be artefacts produced by growth conditions where plants are grown in artificial media such as hydroponics and agar (McCully, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Such sites are reportedly used by some Rhizobium species (e.g. Gopalaswamy et al ., 2000; Vega‐Hernandez et al ., 2001) and fungi (Hessburg & Hansen, 2000; Lagopodi et al ., 2002) to invade hosts. However, these epidermal cracks may not occur naturally in the field or may be artefacts produced by growth conditions where plants are grown in artificial media such as hydroponics and agar (McCully, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with inoculated Douglas-fir seedlings indicate that most minor root wounds no longer act as infection courts after 1 month, because wound closure prevents infection. The pathogen does not penetrate either intact parenchyma or callus (Hessburg and Hansen 2000).…”
Section: Black Stain Root Disease _________mentioning
confidence: 97%
“…Within infection centers, the pathogen spreads by growth in and along roots, by root grafting or root contact, and by limited hyphal growth (up to 15 cm) through the soil between roots (Cobb 1988). Infection can occur through natural openings in small roots, such as splits at root forks and sites where lateral roots emerge, or at the site of root injuries, such as caused by abrasion against rocks (Hessburg and Hansen 2000). Root lesions from Armillaria infections on adjacent trees can also allow transfer of the black stain root disease pathogen from host to host (Hessburg and Hansen 2000).…”
Section: Black Stain Root Disease _________mentioning
confidence: 99%
See 1 more Smart Citation
“…; the aggressive buprestid beetle Phaenops drummondi (Kirby 1837); and the stress-responding bark beetles Dendroctonus pseudotsugae Hopkins, Scolytus unispinosus LeConte, and Pseudohylesinus nebulosus LeConte. Many of these pests are typically opportunistic and secondary (Furniss and Carolin 1977;Shaw and Kile 1991;Hessburg and Hansen 2000), indicating that post-treatment Douglas-fir mortality was related to pre-existing stress compounded by the prescribed fire and subsequent droughts. We observed that patches with mortality of large Douglas-fir resulted in larger openings with little or no tree canopy cover, and these patches were often dominated by shrubs, including blue blossom (Ceanothus thyrsiflorus Eschsch.)…”
Section: Southern Humboldtmentioning
confidence: 99%